Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cb.1717
|View full text |Cite
|
Sign up to set email alerts
|

To share or not to share? Explaining willingness to share in the context of social distance

Abstract: Sharing can help make goods available to many people who would otherwise have no access to them. In the effort of motivating more people to participate in the sharing economy, it is useful to know the variables that influence the willingness to share (WTS). Our study aims to identify these variables. Applying field theory, we conducted an experiment based on nonmonetary sharing situations. Complementing existing research directed towards users of goods, we focused on the providers of goods, thus broadening the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 88 publications
(120 reference statements)
0
19
0
Order By: Relevance
“…Conceptually, this study contributes towards the literature by recognizing the importance of studying both types of one-sided users: consumers and providers. While previous studies have focused on consumers (e.g., Böcker and Meelen, 2017; Edbring et al, 2016; Neunhoeffer and Teubner, 2018) or providers (e.g., Hawlitschek et al, 2016; Karlsson and Dolnicar, 2016; Schreiner et al, 2018), very few studies have investigated both groups simultaneously (e.g., Böcker and Meelen, 2017; Sung et al, 2018) and this is the first study to investigate why one-sided users consider becoming prosumers. The focus on both types of users within our study highlights the potential for platforms to create prosumers from both pools of one-sided users.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Conceptually, this study contributes towards the literature by recognizing the importance of studying both types of one-sided users: consumers and providers. While previous studies have focused on consumers (e.g., Böcker and Meelen, 2017; Edbring et al, 2016; Neunhoeffer and Teubner, 2018) or providers (e.g., Hawlitschek et al, 2016; Karlsson and Dolnicar, 2016; Schreiner et al, 2018), very few studies have investigated both groups simultaneously (e.g., Böcker and Meelen, 2017; Sung et al, 2018) and this is the first study to investigate why one-sided users consider becoming prosumers. The focus on both types of users within our study highlights the potential for platforms to create prosumers from both pools of one-sided users.…”
Section: Discussionmentioning
confidence: 98%
“…Most research in the consumer domain of the sharing economy has examined the motivations for participating in the sharing economy as a consumer (e.g., Böcker and Meelen, 2017; Edbring et al, 2016; Hamari et al, 2016; Neunhoeffer and Teubner, 2018; Ozanne and Ballantine, 2010) or provider (Hawlitschek et al, 2016; Karlsson and Dolnicar, 2016; Schreiner et al, 2018), with the former attracting more attention (Sung et al, 2018). The motivations for both providers and consumers revolve around economic and social reasons, such as cost-saving, profit earning, convenience, availability, sustainability, social interaction and support (Guttentag et al, 2018; Hamari et al, 2016; Ozanne and Ozanne, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tussyadiah (2015), "mistrust between strangers" stands as the critical deterrent to collaborative consumption in the accommodation sector, and marketers should modify touchpoints to deal with the issue of trust. Additionally, Schreiner et al (2018) found that reduced social distance increases individuals' willingness to share. In this framework, sharing more information about the host and confirming the reliability of that information will be critically important for the Couchsurfing platform in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the disparity between self and others increases with social distance. Researchers attribute this phenomenon to a person’s uncertainty toward unfamiliar people (Paek et al, 2005; Schreiner et al, 2018). Prior research found that, when others are perceived as distant, the self-others perceptual gap increased (Andsager and White, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%